Learning-style preference of ESL students - Almasa Mulalic,; Parilah Mohd Shah,; Fauziah Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2009)
Students’ learning styles have been ignored and have been considered as an insigniÞcant component in the learning process (Rita Dunn, 1993). Dunn said that lecturers cannot identify student’s styles without using a multidimensional instrument. Lecturers are not aware of their own learning styles and their learning style preferences may differ from that of their students. As such, they are unable to assess students’ learning styles without administering proper learning styles inventory. Since little attention has been paid to how learners learn and how teachers teach in many institutions, this research attempts to determine the learning styles of the students, and the differences in their learning styles according to gender and ethnicity. This research also aims is to determine the Perceptual Learning Style (PLS) of ESL students and to analyse differences in learning styles regarding student’s demographic factors such as gender and race. In this research, the PLS preferences of ESL students was assessed using the PLSPQ research instrument, which Peacock (2001) reported to be of high reliability. In order to familiarise the readers with the larger picture in determining learning styles, some other relevant research instruments are summarised. One hundred and sixty (N=160) students from UNITEN were selected as respondents using the stratiÞed random sampling techniques. Seventy-four female students (46.3%) and eighty-six male students (53.8%) participated in the research. The racial composition of the samples was 56 Malays (35.0%), 52 Chinese (32.5%) and 52 Indian (32.5%). Results revealed that the dominant learning styles of ESL students yielded the following results. In general, students preferred the Kinaesthetic learning style and expressed minor preference for Visual, Auditory, and Group Learning